ANALISIS INOVASI PELAYANAN ADMINISTRASI KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BEKASI - Aryasatya Nugraha, Krisna; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
Public service innovation is an effort to improve the efficiency, quality, and accessibility of services for the community. Public service innovation is closely related to technological adaptation, particularly through digitalization. The transition from manual to automated public service systems represents progress in creating ideal public services for society. However, public service innovation does not always run smoothly or gain broad acceptance from the public. Problems arise due to the lack of public interest in adapting to and using the latest innovations. The purpose of this study is to analyze and examine innovations in population administration services at the Department of Population and Civil Registration in Bekasi City and to identify the supporting and inhibiting factors affecting these innovations. This study is a descriptive qualitative study, with data collected through observation, interviews, and documentation. The results of the study show that the dimensions of service innovation, such as ease of use, innovation for needs, and innovation for efficiency, have been successfully implemented and optimized. However, the dimensions of relative advantage, compatibility, and use intention are still suboptimal in their implementation, requiring further development and improvement. Supporting and inhibiting factors were also identified in the e-OPen 2.0 innovation. The supporting factors include the willingness to change and the availability of adequate facilities and infrastructure. Meanwhile, the inhibiting factors include administrative pressures and obstacles. These factors highlight the complexity of implementing innovations in public services while emphasizing the need for continuous evaluation and improvement to achieve the desired goals.